Natural rubber bearing incorporated with high toughness steel ring dampers. (April 2020) - Sheikhi, Javad; Fathi, Mojtaba; Rahnavard, Rohola
Abstract: The behavior of natural rubber bearing incorporated with high toughness steel ring dampers (NRB-HTSRDs) is presented. These dampers are made of several steel rings, which are connected by weld in different configurations around the rubber bearing. The operational characteristics of this system including effective horizontal stiffness, secondary hardening, system stability, energy dissipation, equivalent viscous damping, and residual deformation were studied. The results showed that the energy dissipation in these dampers; is mainly revealed as yielding due to flexural deformation of the rings. All specimens of NRB-HTSRDs system; overally enhance the behavior and are considerably better than natural rubber bearing (NRB) or high damping rubber bearing (HDRB). The arrangement of HTSRD2, HTSRD4 and HTSRD6 have better behavior rather than HTSRD1, HTSRD3 and HTSRD5 due to modest initial stiffness at lower shear strains to control small lateral loads of the structure and undesirable effects on the flexibility of rubber bearing, and higher secondary hardening in larger shear strains that increases the energy dissipation and stability of the structure. Also, the specimens in which the rings have larger diameter and are only connected to the top and bottom plates, dissipate energy better than other specimens.